Systematic Literature Review : Machine Learning and Deep Learning Aproaches for Crop Yield Prediction Using Remote Sensing Data - Muhammad Fikri Haikal; Muhammad Ariful Furqon (P3M STMIK LIKMI, 2026)
Accurate crop yield prediction is essential for improving agricultural productivity and food security. This study presents a Systematic Literature Review (SLR) on machine learning and deep learning approaches for crop yield prediction using remote sensing data. Following PRISMA guidelines, 20 high-quality studies published between 2015 and 2025 were analyzed. The results highlight the growing dominance of deep and hybrid models, particularly when multi-source remote sensing data and phenological information are integrated.